Ethics in management consulting - O’Mahoney, Joe (Henry Stewart Talks, 2015)
Critique of management consultancy, Ethics in consulting: the Enron case, Ethical dilemmas & codes, Structural issues: consulting vs. audit, Structural issues: consulting vs. government, The personal cost of consulting